2017
DOI: 10.4103/0366-6999.211555
|View full text |Cite
|
Sign up to set email alerts
|

Current Nondopaminergic Therapeutic Options for Motor Symptoms of Parkinson's Disease

Abstract: Objective:The aim of this study was to summarize recent studies on nondopaminergic options for the treatment of motor symptoms in Parkinson's disease (PD).Data Sources:Papers in English published in PubMed, Cochrane, and Ovid Nursing databases between January 1988 and November 2016 were searched using the following keywords: PD, nondopaminergic therapy, adenosine, glutamatergic, adrenergic, serotoninergic, histaminic, and iron chelator. We also reviewed the ongoing clinical trials in the website of clinicaltri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 127 publications
0
7
0
Order By: Relevance
“…Given the strong impact of EDS, many randomized controlled trials tested different types of possible treatments in these patients: modafinil (Hogl et al., 2002; Ondo et al., 2005; Rodrigues et al., 2016), caffeine (Noyce et al., 2012; Postuma et al., 2012), methylphenidate (Devos et al., 2007), istradefylline (Du & Chen, 2017; Suzuki et al., 2017), and memantine (Ondo et al., 2011), but none of them proved their effectiveness (Seppi et al., 2011; Shen et al., 2018); sodium oxybate showed promising results, but it cannot be considered a first‐choice drug because it is a depressant of the nervous system and respiratory system and has a potential for addiction (Ondo et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Given the strong impact of EDS, many randomized controlled trials tested different types of possible treatments in these patients: modafinil (Hogl et al., 2002; Ondo et al., 2005; Rodrigues et al., 2016), caffeine (Noyce et al., 2012; Postuma et al., 2012), methylphenidate (Devos et al., 2007), istradefylline (Du & Chen, 2017; Suzuki et al., 2017), and memantine (Ondo et al., 2011), but none of them proved their effectiveness (Seppi et al., 2011; Shen et al., 2018); sodium oxybate showed promising results, but it cannot be considered a first‐choice drug because it is a depressant of the nervous system and respiratory system and has a potential for addiction (Ondo et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, extensive studies have focused on the effect of iGluRs in the occurrence and development of PD and put forward that the excitotoxicity of Glu may be one of the important mechanisms in the occurrence and development of PD (Chotibut et al, 2014). Many studies have indicated that although iGluR antagonist has an anti-PD effect, it is still restricted because the receptor is not specifically distributed in the central nervous system, and nonselective iGluR antagonist may have significant side effects, like cognitive dysfunction and psychotomimetic symptoms, in clinical experiments (Du and Chen, 2017; Masilamoni and Smith, 2018). Therefore, researchers have turned to mGluRs and found that mGluR2/3 may be an important target for the treatment of PD (Chan et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…The α-synuclein protein characterizing PD pathogenesis has been found to be overexpressed, with a recent study reporting that the α-synuclein gene (SNCA) combines its 3′-UTR mRNA with miRNA-7, resulting in the inhibition of transcription and protein expression. In PD, given the decrease in miRNA-7 expression, α-synuclein was found to be toxic to dopamine neurons [ 244 , 245 ]. In addition, the blood plasma of patients is enriched in miRNA-4639-5p as a result of the post-transcriptional downregulation of the DJ-1 gene, given that the decrease in DJ-1 protein levels causes severe oxidative stress and neuron death [ 230 ].…”
Section: Pathological Functions Of Exosomesmentioning
confidence: 99%